The domestic blunders of women - Moore, Augustus (C.A. Pearson, 1899)
In spite of the patronizing tone of Moore's discussion of women's domestic incompetence, this book offers some insights into the extent of the work involved in managing a 19th century home and of the need among women for preparation for many of their domestic responsibilities.